2011
DOI: 10.1007/s11703-010-1066-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early feed restriction programs on production performance and hormone level in plasma of broiler chickens

Abstract: Age, duration and intensity of feed restriction of broiler chickens were studied by L 9 (3 4 ) orthogonal experiment. Broiler production performance and meat color were measured to evaluate the effects of feed restriction and explore the superior FR program. A total of 250 1-day-old Ross 308 chicks were selected and randomly allocated to ten groups, including one feed ad libitum (AL) group and nine feed restriction (FR) groups; each group had 5 pens with 5 chickens each. Broilers (T 5 D 7 I 90 ), feed-restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Given the shared response in some measures of the HS and PF groups, the PF treatment as a model of chronic feed restriction may be challenged with nutrients deficiency, resulting in a physiological stress. It has been reported that feed restriction treatment increased the plasma corticosterone concentration just like heat stress …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Given the shared response in some measures of the HS and PF groups, the PF treatment as a model of chronic feed restriction may be challenged with nutrients deficiency, resulting in a physiological stress. It has been reported that feed restriction treatment increased the plasma corticosterone concentration just like heat stress …”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that feed restriction treatment increased the plasma corticosterone concentration just like heat stress. 53,54…”
Section: Discussionmentioning
confidence: 99%
“…The treatments were slow-growing Weining chickens fed ad libitum (SA, n = 50) or under feed restriction (SR, n = 50), as well as fast-growing Jinling chickens fed ad libitum (FA, n = 50) or under feed restriction (FR, n = 50). Feed-restricted birds were restricted from the age of 30 days to 60 days at a level of 70% of the intake of control birds of the same breed [ 14 ]). The ad libitum feed restriction measures were estimated based on our previous study using the same breeds under cage rearing [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The duration, intensity, and timing of feed restriction each have an impact on the growth of chickens [ 13 ]. For example, mild feed restriction of broilers to 90% ad libitum intake for 7 days during early life resulted in the highest body weight, while restriction to 70% for 14 days caused the lowest body weight compared to birds fed ad libitum [ 14 ]. The benefits of alternative feed restriction for chickens are controversial: some authors argue that feed restriction of broilers is commonly applied to promote animal health and decrease feed costs, and thus improve animal welfare [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation